Analysis of Figurative Language and Its Function from a Morphological Perspective by Imagine Dragon in Album Continued Silence - Widyashanti Kunthara Anindita; Muchlishatuz Zahroh (Applied Research on English Education (AREE), 2026)
Using morphological structures like prefixes, suffixes, compounding, and inflection as additional levels of meaning formation, this study aims to investigate metaphorical language in song lyrics. This study employs a descriptive qualitative research methodology. Five chosen songs from the album such as Radioactive, Demons, It's Time, Tiptoe, and Amsterdam were used to gather the data. The analysis uses Perrine's (1963) theory for classifying figurative language types and Bauer's (2019) framework of morphological analysis to examine how word production processes contribute to emotional intensity, thematic coherence, and stylistic impacts. The results indicate that metaphor is the most often used figurative category, with 22 instances out of 50 total figurative words (44 percent). Next are personification (6 occasions), hyperbole (7 instances), and symbolism (9 instances). In terms of morphology, 67% of verbal figurative phrases have the progressive suffix -ing. This suffix transforms static emotional states into dynamic, ongoing processes. 14% of figurative idioms are compound words, which are simplified metaphors. Heartache and daylight are two examples of these concepts. The negative prefix *un-*, which paradoxically emphasizes power while rejecting weakness, is utilized in 16% of cases. The integration of morphological analysis demonstrates that figurative language is not just a semantic or syntactic phenomenon but also a morphological technique for condensing complex emotions into compact linguistic forms. By enabling listeners to process meaning through both lexical and sublexical signals, this approach improves the interpretative experience.Keywords: Figurative language; Imagine Dragons; lyric analysis; Continued Silence; metaphor.